2012
DOI: 10.2298/sarh1210571d
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of non-invasive parameters in patients with left ventricular hypertrophy during a five-year follow-up period

Abstract: In spite of regular medical treatment, patients with larger QTc dispersion, greater septum thickness and lower increase of heart rate during exercise testing showed worse outcome through the follow-up period. These patients should be recognized as early as possible and treated more aggressively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(28 citation statements)
references
References 27 publications
1
25
2
Order By: Relevance
“…Eliakim-Raz et al [27] reported an association between IVS thickening and future development of hypertension in a young healthy cohort of 500 Israeli Air Force aviators and argued that IVS thickening may not merely be a result of long-term BP elevation, but may predict the development of systolic hypertension. In a study of hypertensive patients receiving regular treatment, multivariate adjusted analysis showed that greater IVST at baseline was associated with worse cardiovascular outcomes during 5 years of follow-up [28]. Huang et al [29] concluded that thickened IVS can be served as a reliable marker for predicting all-cause death in Chinese patients with coronary artery disease, even in those with normal LVM.…”
Section: Discussionmentioning
confidence: 99%
“…Eliakim-Raz et al [27] reported an association between IVS thickening and future development of hypertension in a young healthy cohort of 500 Israeli Air Force aviators and argued that IVS thickening may not merely be a result of long-term BP elevation, but may predict the development of systolic hypertension. In a study of hypertensive patients receiving regular treatment, multivariate adjusted analysis showed that greater IVST at baseline was associated with worse cardiovascular outcomes during 5 years of follow-up [28]. Huang et al [29] concluded that thickened IVS can be served as a reliable marker for predicting all-cause death in Chinese patients with coronary artery disease, even in those with normal LVM.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies focusing on patients with particular disease suggested that increased IVS thickness was associated with increased risk of adverse events. For example, in a study of hypertensive patients receiving regular treatment, multivariate adjusted analysis showed that greater IVS thickness at baseline was associated with worse cardiovascular outcomes during 5 years follow up . In a study of patients undergoing isolated aortic valve replacement, van Straten et al .…”
Section: Discussionmentioning
confidence: 99%
“…One hundred twenty‐four patients (average age, 57.0 ± 8.0 years; 84 males and 40 females) were either under 10‐year treatment and monitoring or passed away due to CV events during the monitoring period. A detailed description of the criteria for examination and inclusion of the patients in the study was provided in previously published study, which implied a 5‐year follow‐up of 90 patients . During the period of follow‐up, the basic therapy was changed according to currently valid guidelines for treatment of patients with AH.…”
Section: Methodsmentioning
confidence: 99%
“…An electrocardiogram (ECG) was recorded using EKG‐300 (Electronic Industry Niš, Niš, Serbia) with standard calibration and speed of 50 m/s for calculation of corrected QT interval (QTc) dispersion . The criteria for LVH were applied according to published guidelines (Lyon‐Sokolow score > 38 mm; Cornell product ≥2.440 mm × msec) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation